PROVERB-BASED PICTURE STORYBOOKS FOR STRENGTHENING THE PANCASILA LEARNER PROFILE IN ELEMENTARY LITERACY - Iwan Jazadi; Iga Widari (Nurul Jadid University, 2025)
The implementation of the Kurikulum Merdeka emphasizes the Pancasila Learner Profile as the foundation of character education; however, there remains a lack of culturally responsive literacy materials that integrate local wisdom into early-grade learning. This study aims to develop and evaluate a proverb-based picture storybook grounded in Sumbawanese local wisdom to support elementary students’ literacy and character development. Adopting a design-based research approach, the study involved needs analysis, iterative design and development, expert validation, and classroom trials in four elementary schools. The findings demonstrate that eighteen selected proverbs were systematically transformed into a structured literacy product consisting of denotative explanations, illustrated narratives, connotative interpretations, guided questions, and a teacher guide; the materials were validated as culturally relevant, instructionally feasible, and effective in promoting student engagement and emerging moral understanding. This study presents a validated design model that integrates local proverbs into illustrated literacy materials and offers practical implications for implementing culturally responsive literacy and character education within the Pancasila framework in primary education.